Photography and Heritage: Van Leo Black and White Studio Portraits, 1940s-1970s - Pierandrei, Elisa (I.S. MED. - Interdisciplinary Studies on the Mediterranean, 2023)
In this article, I focus on Van Leo’s photographic practice in the shadow of major political and social changes in the Middle East and North Africa (MENA) region. Born in Jihane, present Turkey, in 1921 Van Leo was an Egyptian photographer with Armenian origins. Although Van Leo took photographs that were mainly of a commercial kind, he brought glamour to the practice of photographic portraiture in the MENA region, inspired by the cinema industry, particularly Hollywood black and white photography. It was in the early 1980s that the transition from black and white to colour photography took place in Egypt. This happened much later when customs restrictions and supply difficulties occurred due to regional conflicts. In those years, Van Leo’s clients were expatriates, Lebanese traders, culture personalities and above all a new generation of aspiring actresses and cabaret soubrettes, sometimes of humble origins, who dreamt of success in theatres or in the fast-growing cinema industry. In post- colonial Egypt, Van Leo embodied a newer generation of Armenian-Egyptian photographers who created glamorous black and white studio portraits, as well as self- portraits that pushed the style to new extremes and extravagances. He thus created a different narrative for his time, echoing and shaping the aesthetic of a nation, its sense of self and the perception of it around the world. This study was conducted researching Van Leo’s collection of photographs available on the Arab Image Foundation online digital archive, as well as through a selection of images from the archive of AUC’s Rare Books and Special Collections Library (RBSCL). This is in addition to examining a new, monumental publication released on the occasion of the 100th anniversary of the photographer’s birth and realized by Karl Bassil in collaboration with Negar Azimi and Katia Boyadjian, titled Becoming Van Leo. Volume I-II-III (Arab Image Foundation and Archive Books, 2021): more than 600 pages of documents (300+), essays by Negar Azimi, Lara Baladi, and Karl Bassil, a few previously unpublished memoirs and interviews, as well as photographs (2380+), and film stills and transcriptions (250+).